The Obverse View: Another Look at Jean-Léon Gérôme's Le 7 décembre 1815, neuf heures du matin [The Execution of Marshal Ney] (1868). (2nd January 2020) - McCallam, David
ABSTRACT: In the light of recent re-evaluations of Jean-Léon Gérôme's practice and significance as a history painter, this article focuses on one of his more controversial and innovative artworks, Le 7 décembre 1815, neuf heures du matin. This painting depicts the immediate aftermath of maréchal Michel Ney's execution by the Restoration regime in 1815. The article reassesses in particular the scandalised reception of the painting in the Paris Salon of 1868 and proposes alternative readings of the artwork's subversive qualities, both for its Second Empire public and for its twentieth-first-century viewers.